Clinical analysis for osmotic demyelination syndrome in patients with chronic hyponatremia - Hsi-Chih Chen; Chih-Chien Sung; Yi-Chang Lin; Lin-Chien Chan; Shih-Hua Lin (Journal of Medical Sciences, 2022)
Background: Although osmotic demyelination syndrome (ODS) has been well known to be associated with a rapid correction of sodium (Na+) in patients with chronic hyponatremia, its risk factors and clinical outcomes have not been examined in Taiwan. Aim: The aim of the study was to analyze the underlying causes and overlooked risk factors in patients with ODS. Methods: We retrospectively collected chronic hyponatremic patients developing ODS and analyzed their clinical characteristics. Results: Fourteen patients (7 males and 7 females) with a mean age of 62.7 ± 17.9 years old were enrolled. Their underlying causes included gastrointestinal illness with poor intake (n = 7), chronic use of diuretics (n = 2), syndrome of inappropriate antidiuretic hormone (n = 2), pneumonia (n = 2), and hypopituitarism (n = 1). Their serum Na+ was 107.2 ± 1.2 mmol/L with mild hypokalemia (potassium 3.1 ± 7 mmol/L), hypoalbuminemia (albumin, 3.4 ± 0.6 g/dL), and hypophosphatemia (phosphorus, 2.3 ± 1.0 mg/dL). Their mean Na+ correction rate was 8.4 ± 9 mmol/L/day and most patients (60%) developed ODS in first 3 days. Their manifestations included delirium, seizures, unstable gait, aphasia, and drowsy consciousness. Brain magnetic resonance imaging demonstrated that 42.8% had isolated central pontine myelinolysis. Totally, 43% of ODS patients had unfavorable outcome with death and disability. In addition, patients with rapid Na+ correction rate (>12 mmol/L/day, n = 4) usually exhibited significant hypokalemia (2.5 ± 0.4 vs. 3.5 ± 0.7 mmol/L, P < 0.05) as compared with those without. Conclusion: Nutritional status and concurrent electrolyte deficiencies such as hypokalemia are major risk factors in patients with ODS. Clinicians should timely recognize these potential risks of ODS and reduce Na+ correction rate to avoid catastrophic outcomes.